ADOPSI DAN PEMANFAATAN TIK BAGI PENGRAJIN KERAMIK DAN GERABAHDIKASONGAN - Djoko Waluyo (Jurnal Masyarakat Telematika dan Informasi, 2010)
This study aimed to determine the process of adoption and use of ICTs by the ceramics craftsmen and businessmen and also pottery at the Pottery Center in Kasongan, Bantu/, Yogyakarta. This research use Qualitative approach with a constructivist paradigm. Research methodology is case study, with the assumption of JCT as a new media especially the Internet in the process of adoption of innovation it takes time to be utilized properly and effectively. Stages of adoption process started from the knowledge acquired informally on the internet, from face to face communication with people who understand the Internet, to the decision to use it was fully decided by the artisans themselves. The study s findings, such as, the use of JCT to access the Internet by the craftsmen is still very limited. The use of internet is usually for e-mail, browsing to find the design of ceramic art in a globalized world, as well as for promotion of ceramic art products. Kasongan ceramic products are mainly for export markets (US., Europe, Korea, Canada, Malaysia) and less for the domestic market (Jakarta, Denpasar, Malang). Routinely, Dinasperindagkop Kab. Bantu/ implement training programs in production engineering and design for the craftsmen to improve the quality of the ceramic products. Kasongan ceramics center area is growing through the concept of Ge/em Kaji, which consists of 3 supporters in the surrounding area (center accessories, leather, pottery and stone sculpture) they all come together as a region center for a more comprehensive Kasongan ceramic products.